Utilización de tres dietas alimenticias en base a forraje hidropónico de cebada y maíz en cuyes durante las etapas de crecimiento y engorde en el centro de experimentación y de producción Salache (Ceypsa) - Ramírez, Erika (2011)
This research was conducted at the Center for Experimental and Production Salache (CEYPSA) in the province of Cotopaxi, we evaluated the effect of three hydroponic forage diets (barley, maize) and control (mixed forage) in stages growing - fattening. Diets were T0 (100% mixed forage), T1 (75% mixed forage + 25% hydroponic forage), T2 (50% % mixed forage + 50 hydroponic forage), T3 (25% mixed forage fodder + 75% hydroponic green). The variables were evaluated during this test animal weight (g), weight gain (g), feed conversion, economic analysis. The management of the experimental units was conducted within the proposed CEYPSA guinea pigs, we proceeded to disinfect the wells designated for the trial of flaming gas, kresso subsequently sprayed with a dose of 1 lt/8 lt water; after 7 days pools are coated with a slurry....